Recursion Operators and Frobenius Manifolds - Magri, F. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
In this note I exhibit a ''discrete homotopy'' which joins the category of F-manifolds to the category of Poisson-Nijenhuis manifolds, passing through the category of Frobenius manifolds.